Creativity in the digital age: A Geographical perspective to the creative processes of new media artists and computer scientists - Wingström, Roosa (fi=Turun yliopisto|en=University of Turku|, 2025)
In this thesis, I study the creative work of new media artists and computer scientists in the digital age. Using a geographical perspective, I consider creativity as a spatio-temporal process during which people, materials, and space interact to produce novel outcomes. This thesis focuses particularly on the role of digital technologies. Digital technologies, such as digital platforms, programs, or devices, can enhance creativity through faster processes, interactions in virtual spaces, and new ways of working. Thus, I scrutinise the socio-material and spatio-temporal contexts that emerge from the use of these technologies and their effect on the creative process. The theoretical and conceptual framework of this thesis combines relevant literature from relational economic geography and digital geographies. I ask: what are the similarities and differences in the creative processes of new media artists and computer scientists; how are the participants’ creative processes enacted through spatio-temporal relations; in what ways do the technologically mediated space-time practices affect the creative processes of the participants; and how can digital technologies, such as artificial intelligence, co-constitute the creative processes of the participants? I utilise interviews, daily diaries, and space-temporal mobility maps to answer these research questions. The findings accentuate the role of digital technologies as co-constitutes in the participants’ creative processes. Digital technologies present several opportunities for the creative process, such as flexible work arrangements as well as novel tools for creative work. The results also identify challenges brought about by digital technologies, as they can disrupt creative work by reducing the time needed for ideation or by interrupting continuous workflow that facilitates concentration. I also suggest how a geographical approach to the creative process can provide a novel insight into the creative process in the digital age. I contend that organising for creativity in the digital age requires recognising the unique space-time configurations and non-human agencies present in creative work. I also call for better recognition of the inherent value of creativity in everyday life, beyond its economic utility.

Luovuus digitaaliaikana: Maantieteellinen näkökulma mediataiteilijoiden ja tietojenkäsittelytieteilijöiden luoviin prosesseihin Tässä väitöskirjassa tutkin mediataiteilijoiden ja tietojenkäsittelytieteilijöiden luovia prosesseja digitaaliajalla. Tarkastelen luovuutta maantieteellisestä näkökulmasta, eli käsitän luovuuden tilallisajallisena prosessina missä uusia lopputuloksia syntyy ihmisten, materiaalien ja tilan vuorovaikutuksessa. Väitöskirjassa keskityn erityisesti digitaalisiin teknologioihin. Digitaaliset teknologiat, kuten digitaaliset alustat, ohjelmat, ja laitteet, voivat tehostaa luovaa työtä esimerkiksi nopeampien prosessien, virtuaalisten tilojen, sekä uusien työskentelytapojen avulla. Tarkastelen teknologian käytöstä syntyviä sosiomateriaalisia ja aikatilallisia konteksteja ja niiden vaikutusta yksilötason luoviin prosesseihin. Väitöskirjani teoreettinen ja käsitteellinen viitekehys yhdistelee keskeistä talousmaantieteen ja digitaalisen maantieteen kirjallisuutta. Esitän neljä tutkimuskysymystä: mitä eroja ja samankaltaisuuksia mediataiteilijoiden ja tietojenkäsittelytieteilijöiden luovissa prosesseissa on; miten he toteuttavat luovia prosessejaan tilan ja ajan eri ulottuvuuksissa; millä tavoin teknologian kanssa syntyvät paikka- ja aikaperustaiset käytännöt vaikuttavat heidän luoviin prosesseihinsa; sekä kuinka digitaaliset teknologiat, kuten tekoäly, osallistuvat näihin luoviin prosesseihin? Vastaan tutkimuskysymyksiin monimenetelmällisesti käyttämällä aineistona haastatteluja, päiväkirjoja sekä liikkuvuutta kuvaavia aikatilakarttoja. Väitöskirjan tuloksissa esitän, kuinka tutkittavien luova prosessi rakentuu yhdessä digitaalisten teknologioiden kanssa. Ihmisen ja teknologian vuorovaikutus tehostaa luovaa prosessia eri tavoin, kuten joustavia työskentelyjärjestelyjä sekä uusia työn tekemisen tapoja mahdollistamalla. Tunnistan myös teknologian tuomia haasteita, esimerkiksi kun ideoimiselle jää vähemmän aikaa tai keskittymistä tukeva katkeamaton työnkulku keskeytyy. Esitän, että maantieteellisillä näkökulmilla voidaan tuottaa uutta tietoa digitaaliajan luovista prosesseista. Digitaaliajan luovan työn organisoinnissa tulee huomioida uniikit tilallisajalliset kontekstit sekä muiden-kuin-ihmisten toimijuus luovissa prosesseissa. Meidän tulee myös paremmin huomioida luovuuden synnynnäinen arvo sen taloudellisen arvon lisäksi.